Preparation and properties of thin films - Tu, K. N. (King-Ning), 1937-; Rosenberg, R. (Treatise on materials science and technology, 1982)
Treatise on Materials Science and Technology, Volume 24: Preparation and Properties of Thin Films covers the progress made in the preparation of thin films and the corresponding study of their properties. The book discusses the preparation and property correlations in thin film; the variation of microstructure of thin films; and the molecular beam epitaxy of superlattices in thin film. The text also describes the epitaxial growth of silicon structures (thermal-, laser-, and electron-beam-induced); the characterization of grain boundaries in bicrystalline thin films; and the mechanical properti.